Dynamics and stability analysis on stairs climbing of wheel–track mobile robot. (17th July 2017) - Gao, Xueshan; Cui, Dengqi; Guo, Wenzeng; Mu, Yu; Li, Bin
A transformable wheel–track robot with the tail rod whose winding will coordinate the center of gravity of the robot is researched, and a theoretical basis for the stable climbing of the robot is provided. After a general introduction of the research, firstly the mechanical hardware and control hardware composition of the wheel–track robot is provided and the principles of its mechanical structure are illustrated. Secondly, through studying the fundamental constrains during the process of the robot climbing the obstacles, a mathematical model based on classical mechanics method is built to help analyze the dynamic principles of a wheel–track mobile robot climbing stairs. Thirdly, the dynamic stability analysis is carried out by analyzing not only the interaction among forces of track, track edge, and stair step but also the different stabilities of the robot when the track and the stairs have different touch points. Finally, an experiment of the modeling track robot climbing the stairs has convinced the effectiveness of the dynamic theories researched, which will be a beneficial reference for the future mobile robots obstacle climbing studies.